Case of catatonia misdiagnosed with coma - Rui Fu; Yanfang Chen; Shaohua Cao (General Psychiatry)
Catatonia is a state of high-degree psychomotor inhibition in which patients often maintain a constant fixed posture, and generally have unconscious obstacles and various reflex preservation. Patients suffering from severe catatonia will become stiff. Catatonia generally manifests unconsciousness while various reflexes are preserved. Patients show reticence, no food or drink intake, and immobility as signs of complete suppression of speech and movement, and even incontinence. Patients are often first diagnosed in non-psychiatric departments and are more likely to be misdiagnosed as having ‘coma’ or ‘epilepsy’, thus delaying treatment. This article reports a case of a 19-year-old female patient who was misdiagnosed with ‘catatonia’. A month ago, she was admitted to a general hospital of our city because of “intermittent attacks of nausea, vomiting, stupor for 15 years, with one week of exacerbation”. During her hospitalisation, she suddenly appeared was mute, had no food or drink intake, and showed immobility and incontinence, presenting a ‘coma state’. She was transferred to a general hospital in Wuhan to further investigate the cause of her “coma”. After 7 days in the hospital, no abnormal examination results were found and the symptoms were not alleviated. Later, she was transferred to the mental health centre for hospitalisation in this city. The patient was diagnosed as having (1) ‘epileptic psychosis’ and (2) ‘catatonic stupor’. After 3 days of treatment, the patient's recovered consciousness. She was clinically cured and discharged half a month later. We hereby report this case.